Основные итоги изучения древней истории, филологии и археологии в Грузии (1967-1977 гг.) - Гиоргадзс, Г. Г.
Giorgadze, G. G. - M. P. Inadze, Main Trends in a Decade of Georgian Studies in Ancient History, Philology and Archaeology; engl. Résumé.